2013
DOI: 10.1097/ipc.0b013e318276959f
|View full text |Cite
|
Sign up to set email alerts
|

Use of Ceftaroline in the Management of Vertebral Osteomyelitis

Abstract: Ceftaroline is a novel broad-spectrum cephalosporin that has activity against gram-negative and gram-positive bacteria including methicillin-resistant Staphylococcus aureus. It was approved by the Food and Drug Administration for the treatment of community-acquired bacterial pneumonia and acute bacterial skin and skin structure infections in October 2010. We report 2 cases of S aureus vertebral osteomyelitis treated effectively with ceftaroline.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 11 publications
1
7
0
Order By: Relevance
“…The results reported here for obese versus nonobese patients also support the conclusion of a previous study that found that dosage adjustment for ceftaroline fosamil based on body weight was not necessary in patients with adequate renal function [21]. In two recent case reports, clinical success was observed with 4 to 6 weeks of ceftaroline fosamil therapy for osteomyelitis using dosing schedules (600 mg twice daily) similar to that used for the majority of patients reported here [16, 17].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The results reported here for obese versus nonobese patients also support the conclusion of a previous study that found that dosage adjustment for ceftaroline fosamil based on body weight was not necessary in patients with adequate renal function [21]. In two recent case reports, clinical success was observed with 4 to 6 weeks of ceftaroline fosamil therapy for osteomyelitis using dosing schedules (600 mg twice daily) similar to that used for the majority of patients reported here [16, 17].…”
Section: Discussionsupporting
confidence: 86%
“…Several recent case reports have described success in the treatment of osteomyelitis with ceftaroline fosamil [16, 17], as have large retrospective observational studies [18, 19]. This retrospective registry study sought to evaluate the experience of patients with osteomyelitis treated with ceftaroline fosamil in Clinical Assessment Program and Teflaro® Utilization REgistry (CAPTURE), a phase 4, multicenter, retrospective cohort study designed to describe the contemporary clinical use of ceftaroline fosamil, including off-label use, in the United States [20].…”
Section: Introductionmentioning
confidence: 99%
“…Several case series of ceftaroline in both standard dose (600 mg IV every 12 hrs) and high dose (600 mg IV every 8 hrs and every 6 hrs) with extended duration (range 4 days to 18 wks) in the treatment of severe MRSA infections have been published to date . Interestingly, ceftaroline was reported to be well tolerated without serious adverse effects despite the similarities in baseline characteristics with our cohort of patients.…”
Section: Discussionmentioning
confidence: 61%
“…Since its approval, ceftaroline has been used as salvage therapy in the treatment of deep‐ seated MRSA infections in multiple case reports . We describe our clinical experience with ceftaroline for the treatment of refractory MRSA and coagulase‐negative Staphylococcus (CoNS) infections.…”
mentioning
confidence: 99%
“…[6][7][8] Recent reports demonstrate the efficacy of ceftaroline fosamil for systemic MRSA infections such as bacteremia, endocarditis, and osteomyelitis. 4,[9][10][11] This case report describes the successful treatment of MRSA bacteremia with ceftaroline fosamil.…”
mentioning
confidence: 98%